Examination of magnitudes of integration in the catarrhine vertebral column. Issue 156 (July 2021) - Jung, Hyunwoo; Simons, Evan A.; von Cramon-Taubadel, Noreen
Abstract: The evolution of novel vertebral morphologies observed in humans and other extant hominoids may be related to changes in the magnitudes and/or patterns of covariation among traits. To examine this, we tested magnitudes of integration in the vertebral column of cercopithecoids and hominoids, including humans. Three-dimensional surface scans of 14 vertebral elements from 30 Cercopithecus, 32 Chlorocebus, 39 Macaca, 45 Hylobates, 31 Pan, and 86 Homo specimens were used. A resampling method was used to generate distributions of integration coefficient of variation scores for vertebral elements individually using interlandmark distances. Interspecific comparisons of mean integration coefficient of variation were conducted using Mann–Whitney U tests with Bonferroni adjustment. The results showed that hominoids generally had lower mean integration coefficient of variation than cercopithecoids. In addition, humans showed lower mean integration coefficient of variation than other hominoids in their last thoracic and lumbar vertebrae. Cercopithecoids and Hylobates showed relatively lower mean integration coefficient of variation in cervical vertebrae than in thoracolumbar vertebrae. Pan and Homo showed relatively lower mean integration coefficient of variation in the last thoracic and lumbar vertebrae in the thoracolumbar region, except for the L1 of Pan . The results suggest fewer integration-mediated constraints on the evolution of vertebral morphology in hominoids when compared with cercopithecoids. The weaker magnitudes of integration in lumbar vertebrae in humans when compared with chimpanzees likewise suggest fewer constraints on the evolution of novel lumbar vertebrae morphology in humans.